DANDELION AND ITS HEALING PROPERTIES AND APPLICATION IN THE PHARMACEUTICAL INDUSTRY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article describes dandelion and its medicinal properties, as well as its use in the pharmaceutical industry and its medicinal properties.